2008
DOI: 10.1007/s12247-008-9042-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterisation of a Newly Isolated Stable Long-Life Tannase produced by F. subglutinans (Wollenweber and Reinking) Nelson et al.

Abstract: A stable long-life tannase was synthesised by Fusarium subglutinans and the fermentation processing parameters were optimised. Maximum enzyme production (9.38 U/ml) was recorded after 96 h of incubation at 35°C, initial pH 5, in submerged culture (200 rpm) utilising 2% (w/v) tannic acid as a sole carbon source. The tannase produced was purified to electrophoretic homogeneity through two-step column chromatography and the purified form remained stable in a pH range of 6-8. Its midpoint of thermal inactivation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Rajkumar and Nandy obtained a yield of 69% with ammonium sulphate precipitation [ 18 ]. Hamdy reported that 65% ammonium sulphate was optimum for tannase precipitation [ 19 ]. Sabu et al [ 20 ] found 4-fold purification yield of the dialyzed tannase with specific activity of 0.916 U/mg protein.…”
Section: Resultsmentioning
confidence: 99%
“…Rajkumar and Nandy obtained a yield of 69% with ammonium sulphate precipitation [ 18 ]. Hamdy reported that 65% ammonium sulphate was optimum for tannase precipitation [ 19 ]. Sabu et al [ 20 ] found 4-fold purification yield of the dialyzed tannase with specific activity of 0.916 U/mg protein.…”
Section: Resultsmentioning
confidence: 99%
“…However, the value of V max /K m was better for methyl-gallate, revealing that the catalytic cycle is faster in this substrate than in the presence of tannic acid and propyl-gallate. The affinity of the extracellular enzyme from A. phoenicis to tannic acid was two times higher than that observed for the enzyme produced by Fusarium subglutinans [39], and 19 times higher than that obtained for the enzyme from P. variable [33]. In the presence of methyl gallate, the affinity was similar to the enzyme from P. variable [33] but lower when compared to the tannases from A. niger [24] and A. oryzae [40], among others.…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…The addition of Mg +2 increased the tannase activity, but it is still unclear whether if it acts as a cofactor or if it has a nonspecific effect (Kar et al 2003;Mukherjee and Banerjee 2006;Naidu et al 2008;Hamdy 2008) …”
Section: Mechanism Of Actionmentioning
confidence: 99%